Pueraria mirifica inhibits 17β-estradiol-induced cell proliferation of human endometrial mesenchymal stem cells - Ta-Chin Lin; Kai-Hung Wang; An-Pei Kao; Kuo-Hsiang Chuang; Tsung-Cheng Kuo (Elsevier, 2017)
Objective: The notion that the human endometrium may contain a population of stem cells has recently been proposed. The mesenchymal stem cells (MSCs) in the endometrium are believed to be responsible for the remarkable regenerative ability of endometrial cells. Estrogens influence the physiological and pathological processes of several hormone-dependent tissues, such as the endometrium. Pueraria mirifica (PM) is a herbal plant that contains several phytoestrogens, including isoflavones, lignans, and coumestans, and is known to exert an estrogenic effect on animal models. The present study investigated the effects of PM on the proliferation of human endometrial MSCs (hEN-MSCs). Materials and methods: The hEN-MSCs were isolated from human endometrial tissue. The surface markers of these hEN-MSCs were identified through reverse transcription-polymerase chain reaction analysis. The proliferation potential of hEN-MSCs was measured through a cell proliferation assay. Multilineage differentiation ability was confirmed through Oil red O and von Kossa staining. Results: This study demonstrated that 17β-estradiol-responsive MSCs with Oct-4, CD90, and CD105 gene expression can be derived from the human endometrium and that PM exerts biological effects on hEN-MSCs, specifically, enhanced cell growth rate, through the estrogen receptor. Furthermore, PM at 1500 and 2000 μg/mL significantly increased cell proliferation compared with the vehicle control, and PM concentration at 1000 μg/mL significantly inhibited the enhanced cell growth rate induced by 17β-estradiol in hEN-MSCs. Conclusion: This study provides new insights into the possible biological effects of PM on the proliferation of hEN-MSCs.